MANAJEMEN KESISWAAN DALAM PENINGKATAN PRESTASI AKADEMIK DAN NON AKADEMIK SISWA DI MAN 2 KOTA MALANG - Uswatun Hasanah . (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of writing this article is to determine the role of student management in improving academic and non-academic achievements. This study uses a qualitative descriptive method with data collection techniques Observation, interviews, and documentation. The research location is in Madrasah Aliyah Negeri 2 Malang City. The steps are collecting information or collecting classification data, analyzing data, making conclusions and reporting. The results showed that the planning of this program was carried out by formulating the vision, mission, and goals of the madrasa, planning several programs of special activities in improving students' academic and non-academic achievements.